Assessing the effectiveness of molecular data for species identification and diversity studies of Nigerian herpetofauna. Issue 1 (2nd January 2019) - Nneji, Lotanna M.; Adeola, Adeniyi C.; Okeyoyin, Agboola O.; Oladipo, Ojo C.; Saidu, Yohanna; Usongo, John Y.; Ugwumba, Adiaha A. A.
Abstract: We evaluated the effectiveness of molecular data (mitochondrial cytochrome c oxidase subunit I – COI and 16S ribosomal RNA – 16S) for species identification and diversity studies of Nigerian herpetofauna. We collected 189 specimens consisting of 91 amphibians and 98 reptiles from the largest and under-studied national park in Nigeria – Gashaka Gumti National Park (GGNP), eastern Nigeria. The resulting COI and 16S data allowed us to compare our sequences with others in global databases for species identification. During query searches, we observed poor representation of COI sequences for African herpetofauna in the GenBank and BOLD databases. Neighbour-joining (NJ) trees constructed based on COI and 16S datasets for all specimens sequenced for this study clustered most individuals of the same species. On the other hand, morphologically unidentified amphibian ( Leptopelis sp and Ptychadena sp) and reptile ( Hemidactylus sp and Lycophidion sp) species formed strongly supported lineages in the NJ trees, and were clearly separated from their sister species. Further, the NJ tree-based analyses recovered at least two well supported divergent lineages within Agama agama and Trachylepis maculilabris . Our study confirms the efficiency of integrating morphological and DNA barcoding approaches in identification and diversity studies of Nigerian herpetofauna. Finally, we recommend development of comprehensive and reliable DNA barcode reference libraries for global amphibians and reptiles.